1987
DOI: 10.1042/bj2410075
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptidyl peptidase II in haemolysates and liver homogenates of various species

Abstract: Rabbit antibodies against purified tripeptidyl peptidase II (TPP II) of human erythrocytes have been prepared and used in immunoblot analysis. Antibodies affinity-purified against the denatured 135,000-Mr subunit of the human peptidase were shown to cross-react with purified rat liver TPP II, as well as a polypeptide of Mr 135,000 in haemolysates and liver homogenates from several other species. TPP II activity in haemolysates from monkey, hog, horse and rabbit corresponded to the levels found in human erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The assembled enzyme functions as an exopeptidase that removes tripeptides from the free N-terminus of polypeptides (Balow and Eriksson, 1987; Balow et al 1983; Balow et al 1986; Tomkinson et al 1997), but also exhibits endopeptidase activity towards long peptides (Geier et al 1999; Seifert et al 2003). We have previously demonstrated that overexpression of TPPII in Burkitt’s lymphoma or transfected HEK293 cells correlates with accelerated proliferation and with the accumulation of centrosome and chromosome aberrations, whereas functional knockdown of TPPII by shRNA results in growth retardation and the accumulation of polynucleated cells that fail to complete cell division (Stavropoulou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The assembled enzyme functions as an exopeptidase that removes tripeptides from the free N-terminus of polypeptides (Balow and Eriksson, 1987; Balow et al 1983; Balow et al 1986; Tomkinson et al 1997), but also exhibits endopeptidase activity towards long peptides (Geier et al 1999; Seifert et al 2003). We have previously demonstrated that overexpression of TPPII in Burkitt’s lymphoma or transfected HEK293 cells correlates with accelerated proliferation and with the accumulation of centrosome and chromosome aberrations, whereas functional knockdown of TPPII by shRNA results in growth retardation and the accumulation of polynucleated cells that fail to complete cell division (Stavropoulou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Tripeptidyl‐peptidase II (TPP II) (EC 3.4.14.10) is an enzyme with remarkable characteristics. It was discovered 1983 as an extralysosomal peptidase in rat liver [1] and has since been extensively characterized [2–6]. It is one of only two known mammalian tripeptide‐releasing enzymes (reviewed in [7]).…”
mentioning
confidence: 99%
“…Both fragments are biologically inactive. The discovery of tripeptidyl peptidase II in rat liver cytosol was first reported in 1983 and the enzyme has been extensively characterized since then [6][7][8][9]. It is an extralysosomal serine peptidase with an active site of the subtilisin type.…”
Section: Introductionmentioning
confidence: 99%